Novel Insights into Total Flavonoids of Rhizoma Drynariae against Meat Quality Deterioration Caused by Dietary Aflatoxin B1 Exposure in Chickens - Ke Yue; Kai-Li Liu; Yao-Di Zhu; Wen-Li Ding; Bo-Wen Xu; Aftab Shaukat; Yan-Feng He; Lu-Xi Lin; Cai Zhang; Shu-Cheng Huang (MDPI AG, 2022)
Aflatoxin B1 (AFB1) is a group of highly toxic mycotoxins that are commonly found in human and animal foods and threaten animal and human food safety. Total flavonoids of Rhizoma Drynaria (TFRD), a traditional Chinese medicinal herb, exert multiple biological activities such as immunomodulatory, anti-inflammatory, and anti-oxidation effects. Here, a total of 160 healthy 21-day-old male broilers were randomly divided into four groups: the CON group, the TFRD group, the AFB1 group, and the AFB1 + TFRD group. The study found that AFB1 exposure altered the breast meat quality-related indicators, including meat sensory and physical indicators. Metabolomics analysis further showed that the change in meat quality was closely associated with significantly differential metabolites of breast muscle. Furthermore, spotlighted amino acid content contributes to changes in the secondary structure of the myofibrillar protein by Raman spectroscopy analysis, which was associated with the oxidative stress and inflammatory response in AFB1-exposed breast meat. Meanwhile, dietary 125 mg/kg TFRD supplementation could effectively restore the changes in breast meat quality. Taken together, these results by multi-technical analysis revealed that AFB1 exposure causes deterioration of chicken meat quality and that TFRD may be a potential herbal extract to antagonize mycotoxicity.